Waste tyre rubber in asphalt pavement modification - Mashaan, N.S.; Karim, M.R. (Maney Publishing, 2014)
Currently, a serious problem that leads to environmental pollution is the abundance and increase of waste tyres from vehicles. The major approach to solve this issue is to recycle waste tyre rubber including its use as crumb rubber modifier in asphalt pavement. This study aims to investigate the effect of crumb rubber modifier on engineering properties of rubberised asphalt. The physical and rheological properties of rubberised asphalt binder that include different percentages of crumb rubber modifier (0, 4, 8, 12, 16 and 20%) were determined and assessed using various laboratory tests. Results showed that 16% crumb rubber modifier at 180 degrees C blending temperature have a significant effect on modified binder engineering properties. Also, the study promotes the recycle of waste tyre rubber in an environment friendly manner.